Quatre inscriptions sabéennes provenant d'un temple de Dhu-Samawi - Bron, François (Syria, 1997)
Publication of four bronze plates coming from a temple of the god dhu-Samawi, situated in the wadi Shudayf, to the north of the Jawf (Yemen). One is a commonplace dedication to the god, but the three others are penitential texts of the kind studied by J. Ryckmans. In two of them, the dedi- cant confesses to having contravened the rules of ritual purity. The last one is partly broken and seems to mention a pilgrimage.